Chance in mineral content in Lathyrus sativus infected with Peronospora lathyri-palustris - S.P. SINGH**, S. KUMAR***; R.L. PRASAD, B.K. PRASAD, SHAMBHU DAYAL, N.P. SINHA* (Indian Phytopathology, 2002)
Nitrogen was found to be deficient in diseased leaflets on the tenth day after appearance of the symptom. Phosphorus, potassium, and calcium remained unchanged in diseased and healthy leaflets. Zinc, manganese and copper became gradually less in the former in contrast to the latter in which the trend was reversed. Iron was found to be gradually increasing in diseased leaflets while decreasing in healthy ones.